Hybrid 0D Antimony Halides as Air‐Stable Luminophores for High‐Spatial‐Resolution Remote Thermography. Issue 9 (22nd January 2021) - Morad, Viktoriia; Yakunin, Sergii; Benin, Bogdan M.; Shynkarenko, Yevhen; Grotevent, Matthias J.; Shorubalko, Ivan; Boehme, Simon C.; Kovalenko, Maksym V.
Abstract: Luminescent organic–inorganic low‐dimensional ns 2 metal halides are of rising interest as thermographic phosphors. The intrinsic nature of the excitonic self‐trapping provides for reliable temperature sensing due to the existence of a temperature range, typically 50–100 K wide, in which the luminescence lifetimes (and quantum yields) are steeply temperature‐dependent. This sensitivity range can be adjusted from cryogenic temperatures to above room temperature by structural engineering, thus enabling diverse thermometric and thermographic applications ranging from protein crystallography to diagnostics in microelectronics. Owing to the stable oxidation state of Sb 3+, Sb(III)‐based halides are far more attractive than all major non‐heavy‐metal alternatives (Sn‐, Ge‐, Bi‐based halides). In this work, the relationship between the luminescence characteristics and crystal structure and microstructure of TPP2 SbBr5 (TPP = tetraphenylphosphonium) is established, and then its potential is showcased as environmentally stable and robust phosphor for remote thermography. The material is easily processable into thin films, which is highly beneficial for high‐spatial‐resolution remote thermography. In particular, a compelling combination of high spatial resolution (1 µ m) and high thermometric precision (high specific sensitivities of 0.03–0.04 K −1 ) is demonstrated by fluorescence‐lifetime imaging of a heated resistive pattern on a flat substrate, covered with a solution‐spun film of TPP2 SbBr5 . Abstract : Luminescent organic–inorganic low‐dimensional ns 2 metal halides are increasingly explored as thermal phosphors for high‐resolution remote thermography and thermometry due to the high thermal sensitivity of their radiative lifetime. Thin films of such hybrids, conformally coating the surface of interest, can map the temperature with a spatial precision as high as 1 μm using fluorescence‐lifetime imaging.